Inventory Management Practices and the Performance of Scall-Scale Businesses: A Case Study of Nasuuti in Mukono Municipality - Felicia Nabbosa (Uganda Christian University, 2023)
The study examined the effect of inventory management practices on the performance of Small Scale Businesses in Mukono. It specifically focused on; establishing the contribution of inventory recording and the performance of SSBs, finding out the contribution of inventory planning and scheduling on the performance of SSBs and determining the contribution of inventory costs on the performance of SSBs. The study was carried out using a cross sectional survey research design where quantitative research approach was also used. The data was collected using questionnaires during the data collection, stratified sampling method was used. A sample size of 32 respondents who are SSB owners in Nasuuti, Mukono Municipality was also used in the study. From the findings, the study revealed that inventory recording greatly contributes to the performance of SSBs in Nasuutisince inventory recording helps in maintaining inventory records which are updated regularly in business and given that it helps in comparing the money received with the total cash sales in the businesses which enhances business profitability. it was revealed that inventory planning and scheduling greatly contributes to the performance of SSBs in Nasuuti since inventory planning and scheduling enhances the setting of a good stock plan in advance and given that it enables the business to conduct regular stock counts which has enhanced cost reduction the businesses.Finally, it can be concluded that inventory costs greatly contributes to the performance of SSBs in Nasuutiwhere businesses that implement inventory control systems can have lower costs which enhances business profitability. The study recommended that owners of SSBs in Nasuuti and other businesses in different areas should install a computerized package to deal with recording of inventory so as to avoid unintentional errors. The study also recommends that the owners of SSBs need to ensure that the stores are enlarged and tidy so as to ensure maximum usage of space among others. Lastly, there is need to avoid duplication of records due to price variance, the FIFO (first in first out) and LIFO (last in first out) system of issues should be adopted.
This is a dissertation.